2016
DOI: 10.1002/1873-3468.12386
|View full text |Cite
|
Sign up to set email alerts
|

Dual substrate‐controlled kinase activity leads to polyphosphorylated lasso peptides

Abstract: Edited by Alfonso ValenciaLasso peptides are characterized by their peculiar lariat knot-like structure. Except for maturation of this fold, post-translational modifications of lasso peptides are rare. However, we recently delineated the biosynthetic pathway of a post-translationally phosphorylated lasso peptide, paeninodin. In this study, further investigation of two kinases revealed their ability to transfer multiple phosphate groups onto precursor peptide substrates, ultimately leading to polyphosphorylated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 46 publications
2
26
1
1
Order By: Relevance
“…Past research has shown that bioinformatics studies could readily identify novel RiPPs using homology searching methods [15]. For example, novel modified lasso peptides, such as phosphorylated and acetylated lasso peptides, were discovered using this strategy [24][25][26]. However, completely new families of RiPPs have not been discovered by these strategies, which hinders the progress of RiPP research.…”
Section: Introductionmentioning
confidence: 99%
“…Past research has shown that bioinformatics studies could readily identify novel RiPPs using homology searching methods [15]. For example, novel modified lasso peptides, such as phosphorylated and acetylated lasso peptides, were discovered using this strategy [24][25][26]. However, completely new families of RiPPs have not been discovered by these strategies, which hinders the progress of RiPP research.…”
Section: Introductionmentioning
confidence: 99%
“…Another recently identified series of proteobacterial lasso peptides, including astexin-1, sphingopyxin I, and caulosegnin I, are synthesized from gene clusters that feature a lasso peptide-specific isopeptidase instead of an ABC transporter 12 15 18 19 33 34 35 36 37 . Yet another putative, proteobacterial gene cluster features a lasso peptide-tailoring kinase (K) with A B1 B2 C K D organization 19 24 38 . Here, the “split” B1 and B2 proteins share homology with the N- and C-terminal domains of an “intact” B protein, respectively.…”
mentioning
confidence: 99%
“…Split B proteins were also observed in actinobacterial clusters such as those producing lariatin, sviceucin, and streptomonomicin (A C B1 B2 D organization) as well as firmicute clusters (C A K B1 B2 D organization) such as that of paeninodin 11 13 39 40 . Kinases from the latter were recently characterized as tailoring enzymes of lasso peptide precursors, ultimately yielding phosphorylated lasso peptides 24 38 . A general schematic for the proposed route of lasso peptide biosynthesis is presented in Fig.…”
mentioning
confidence: 99%
“…The predicted sequence of PsmA ends with an asparagine residue as opposed to C-terminal serine of paeninodin precursor PadeA, which is subject to phosphorylation. 14,17 We resequenced the psmA gene and found a single nucleotide difference with the published sequence at the last codon. The correct sequence in fact codes for a PsmA peptide with a terminal serine.…”
Section: Resultsmentioning
confidence: 99%